Bacteriological and histopathological investigations of liver abscesses - Lechtenberg, K.F.; Leipold, H.W.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fusobacterium necrophorum was the predominant bacterial isolate from 49 liver abscesses. Biotype A tended to occur in pure infections and produced a more severe tissue reaction than biotype B, which tended to occur as a mixed infection.
Keywords: Beef; Liver abscesses; Bacteria